Trends in Harnessing Plant Endophytic Microbiome for Heavy Metal Mitigation in Plants: A Perspective - Pragya Tiwari; Hanhong Bae (Plants, 2023)
Plant microbiomes represent dynamic entities, influenced by the environmental stimuli and stresses in the surrounding conditions. Studies have suggested the benefits of commensal microbes in improving the overall fitness of plants, besides beneficial effects on plant adaptability and survival in challenging environmental conditions. The concept of ‘Defense biome’ has been proposed to include the plant-associated microbes that increase in response to plant stress and which need to be further explored for their role in plant fitness. Plant-associated endophytes are the emerging candidates, playing a pivotal role in plant growth, adaptability to challenging environmental conditions, and productivity, as well as showing tolerance to biotic and abiotic stresses. In this article, efforts have been made to discuss and understand the implications of stress-induced changes in plant endophytic microbiome, providing key insights into the effects of heavy metals on plant endophytic dynamics and how these beneficial microbes provide a prospective solution in the tolerance and mitigation of heavy metal in contaminated sites.